Idala: an unnamed function peptide vaccine for tuberculosis - Abdulla, Mahmood Ameen; Ismail, S.; Darwish, N.T.; Teow, C.T.; Omar, R. (Pharmacotherapy Group, University of Benin, Benin City, 2012)
Purpose: To evaluate Myt272 protein antigenicity and immunogenicity by trial vaccination in mice and its in silico analysis as a potential peptide vaccine for tuberculosis. Methods: Myt272 gene, which has 100 % identity with Mycobacterium tuberculosis H37Rv unknown function gene Rv3424c, was ligated by genomic shotgun approach into the expression vector pQE32, and transformed into Escherichia coli SG13009. Expression during cell growth was induced by isopropyl-β-D-thiogalactopyranoside. The recombinant protein was isolated from the harvested cell lysate and injected in mice for immunogenicity experiment up to 42 days. ELISA tests with anti-His antibodies were performed on the collected individual blood samples’ sera. Color development in a microplate reader was measured at 450 nm. Results: The protein was predicted to have a mass of approximately 13 kDa and was present in the soluble fraction of the cell lysate. The immunogenicity test on Myt272 protein revealed very statistically significant high levels of antibodies detected by ELISA in the sera of immunized group of mice compared to negative controls. Conclusion: A 10.1 kD unnamed function (IDALA) protein from Rv3424 gene could be the potential peptide vaccine for tuberculosis tested by mice immunogenicity experiment.